(untitled) (Wageningen, 1996)
This report is written for the project MHO-8 IMCR (Integrated Management of Coastal Resources in the Mekong Delta, Vietnam). This project is a cooperation of WAU, The Netherlands and CTU, Vietnam. The project has as a general objective to contribute to the alleviation of the problems faced by the people living in the salt water intruded part of the Mekong Delta. Three types of activities will be engaged in: training, curriculum development and research. The project selected an area for research which is the Vinh Loi district, Minh Hai province, Mekong Delta, Vietnam.
Keywords: Soil acidity,Soil science